FTO Gene Polymorphisms Contribute to the Predisposition and Radiotherapy Efficiency of Nasopharyngeal Carcinoma - Xiao F; Zhou J (Dove Medical Press, 2021)
Feng Xiao, Jianrong Zhou School of Nursing, Chongqing Medical University, Chongqing, 400016, People's Republic of ChinaCorrespondence: Jianrong ZhouSchool of Nursing, Chongqing Medical University, No. 1 Changda Road, Jiulongpo District, Chongqing, 400016, People's Republic of ChinaEmail jianrong_zhou@21cn.comBackground: Nasopharyngeal carcinoma (NPC) is mainly concentrated in East and Southeast Asia. This study aims to elucidate the potential associations of functional SNPs in the fat mass and obesity associated gene (FTO) with NPC risk and radiotherapy outcomes in a Chinese population.Methods: Functional SNP rs1477196 G>A, rs9939609 T>A, rs7206790 C>G, and rs8047395 A>G were genotyped and evaluated for their associations with NPC risk and radiotherapy outcomes.Results: Both rs9939609 (allele A versus allele T: OR=1.59; 95% CI=1.17- 2.17; P-value=0.003) and rs8047395 (allele G versus allele A: OR=0.76; 95% CI=0.64- 0.9; P-value=0.002) were significantly associated with risk of NPC. GTEx showed risk allele A of rs9939609 and rs8047395 were significantly associated with higher FTO mRNA levels in skeletal muscle tissue, which also corroborated our findings. Meanwhile, both rs1477196 (allele A versus allele G: OR=1.64; 95% CI=1.09- 2.49; P-value=0.019) and rs9939609 (allele A versus allele T: OR=0.61; 95% CI=0.43- 0.87; P-value=0.006) were significantly associated with complete remission (CR) of NPC.Conclusion: Our study identified that FTO polymorphisms contributed to the susceptibility and radiotherapy efficacy of NPC. These results shed light on the potential of establishing markers for predicting risk and personalized treatment of NPC.Keywords: nasopharyngeal carcinoma, FTO, predisposition, radiotherapy